2019
DOI: 10.1109/access.2019.2928015
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Analysis Associated With the Ecuador Earthquake Using Swarm A and C Satellite Magnetic Data Based on PCA

Abstract: In this paper, we revisit this earthquake by simultaneously analyzing the magnetic field data of Swarm satellite A and satellite C based on principal component analysis (PCA), and the eigenvalues and principal components are calculated throughout 2016. We find that the first principal component mainly contains the signal originating from solar-terrestrial effects such as geomagnetic activity since the first eigenvalue and the geomagnetic index are highly correlated. Therefore, the second principal component is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Moreover, weather phenomena could move and mix the substances released from underground into the atmosphere could mask precursors, if any, lowering their signal-tonoise ratio and shortening their persistence in the atmosphere (Marchetti et al, 2019). Similar results have been obtained by De Santis et al ( 2020) that have applied a multi-parametric study to the 2019 M7.1 Ridgecrest earthquake, by analysing furthermore methane exhalations [as suggested by Cui et al (2019)], electron density fluctuations, and magnetic field measurements from Swarm satellites (Friis-Christensen et al, 2006;Zhu et al, 2019). The results can be summarized as follows: 1) precursor times would be much longer than those identified by other papers (especially about ionospheric precursors which seem to occur only a few hours to days before large seismic events) (see for example Heki, 2011;He and Heki, 2017;Yan R. et al, 2017); 2) the preparation phase would be much longer than few days [as also suggested by Liu et al (2020), Marchetti et al (2019), Marchetti et al (2020), Sugan et al (2014), Giovambattista and Tyupkin (2004)]; claimed precursors would follow the empirical Rikitake (1987) law, recently confirmed for ionospheric precursors from the satellite by De Santis et al (2019a).…”
Section: Multi-parametric Analyses Looking For Earthquake Precursorssupporting
confidence: 73%
“…Moreover, weather phenomena could move and mix the substances released from underground into the atmosphere could mask precursors, if any, lowering their signal-tonoise ratio and shortening their persistence in the atmosphere (Marchetti et al, 2019). Similar results have been obtained by De Santis et al ( 2020) that have applied a multi-parametric study to the 2019 M7.1 Ridgecrest earthquake, by analysing furthermore methane exhalations [as suggested by Cui et al (2019)], electron density fluctuations, and magnetic field measurements from Swarm satellites (Friis-Christensen et al, 2006;Zhu et al, 2019). The results can be summarized as follows: 1) precursor times would be much longer than those identified by other papers (especially about ionospheric precursors which seem to occur only a few hours to days before large seismic events) (see for example Heki, 2011;He and Heki, 2017;Yan R. et al, 2017); 2) the preparation phase would be much longer than few days [as also suggested by Liu et al (2020), Marchetti et al (2019), Marchetti et al (2020), Sugan et al (2014), Giovambattista and Tyupkin (2004)]; claimed precursors would follow the empirical Rikitake (1987) law, recently confirmed for ionospheric precursors from the satellite by De Santis et al (2019a).…”
Section: Multi-parametric Analyses Looking For Earthquake Precursorssupporting
confidence: 73%
“…In that study, the cumulative number of orbits with anomalies inside that region showed an acceleration before the Ecuador earthquake and recovered to a linear (i.e., standard) trend after the earthquake. In addition to the aforementioned examples, numerous studies have confirmed that the Swarm ionospheric perturbations are sensitive enough and useful for detecting earthquake-related anomalies, such as for the 2014 Ludian earthquake [8], 2017 Sarpol-e Zahab (Iran) earthquake [9], 2017 Mexico earthquake [10], and the above mentioned 2016 Ecuador earthquake [11,12].…”
Section: Introductionmentioning
confidence: 89%
“…When several variables must be studied in order identify the "prevailing" ones and possible correlations, the principal component analysis (PCA) could be adopted for analyzing time series of observations and to reject background noise. After Hattori et al (2004), that applied PCA to ground based observation of magnetic data, more recently, Zhu et al (2019) applied PCA to Swarm satellite (Friis-Christensen et al, 2008) magnetic field data successfully finding seismo-related anomalies.…”
Section: Ionospheric Disturbancesmentioning
confidence: 99%